2020
DOI: 10.1002/ece3.6701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wind farms on wintering ducks at an important wintering ground in China along the East Asian–Australasian Flyway

Abstract: Wind farms offer a cleaner alternative to fossil fuels and can mitigate their negative effects on climate change. However, wind farms may have negative impacts on birds. The East China Coast forms a key part of the East Asian–Australasian Flyway, and it is a crucial region for wind energy development in China. However, despite ducks being the dominant animal taxon along the East China Coast in winter and considered as particularly vulnerable to the effects of wind farms, the potential negative impacts of wind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 95 publications
1
13
0
Order By: Relevance
“…Bird movements are driven by food resources and habitats, which are also influenced by anthropogenic facilities (e.g. wind farms) [17, 53]. The current results showed that distance between ducks’ geographic locations and the nearest wind turbines in the middle and later wintering periods tended to increase significantly (Figure 3), suggesting dynamic avoidance by ducks to decrease overlap with onshore wind farms.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Bird movements are driven by food resources and habitats, which are also influenced by anthropogenic facilities (e.g. wind farms) [17, 53]. The current results showed that distance between ducks’ geographic locations and the nearest wind turbines in the middle and later wintering periods tended to increase significantly (Figure 3), suggesting dynamic avoidance by ducks to decrease overlap with onshore wind farms.…”
Section: Discussionmentioning
confidence: 71%
“…During December 2019 and January 2020, we conducted six field surveys of flight‐height observations at four fixed observation sites during dawn (04:00–06:00) and dusk (17:30–19:30) on sunny days, without strong wind or heavy fog. The average distance between adjacent wind turbines in the Yangtze River Mouth, China, was 500 m [17], and we therefore selected fixed observation sites between adjacent wind turbines. We defined the wind farm status on both sides of the fixed observation points as turned on or off.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations